Planning for The Development of the Bondok Classroom Boarding School Al Asror Arromah Patemon - Nugradi, Didik Nopianto Agung; Diharto, Diharto; Santoso, Eko Budi; Prihanto, Teguh; Firmansyah, Aldy; Ikhsan, Mahbub Amrulloh; Nurhayati, Novika (Jurnal Abdimas, 2025)
Islamic boarding schools play a strategic role in character formation and the development of knowledge based on religious values. Asror Arrohmah Patemon, Semarang, moment This face constraint limitations room facilities the class that not enough optimal in support activity Study teach. Community service program public This aim For designing development room more functional, comfortable, and environmentally friendly classrooms. The implementation method involves surveying existing conditions, analyzing needs, planning floor plans, creating 3D models, and preparing a Cost Budget Plan (RAB). The planning results show classroom designs that apply green building principles, such as natural lighting, cross-ventilation, and efficient spatial planning. 3D visualization makes it easier for management to understand the design, evaluate technical and aesthetic aspects, and planning the construction phase. In conclusion, this activity resulted in a representative design that supports the student learning process and creates a conducive and sustainable educational environment.